MENINGKATKAN KETERAMPILAN MEMBUAT KERIPIK KENTANG MELALUI METODE LATIHAN BAGI ANAK TUNARUNGU - Aspuriyah Aspuriyah; Kasiyati Kasiyati; Fatmawati Fatmawati (Universitas Negeri Padang, 2013)
This study aimed to: 1) Determine the implementation process in improving skills to make potato chips through training methods and 2) prove that the method of exercises can improve the skills of making potato chips in deaf children class V SDLB 20 Nanbalimo Solok City.This study removed using action research method (Classroom Action Research) conducted in collaboration with colleagues. Data were collected through observation and testing techniques, and then analyzed qualitatively and quantitatively. The results showed that 1) the implementation process in improving skills to make potato chips through training methods done in two cycles. Cycle I conducted five meetings with the goal of cycle